A Mixed Integer Programming Model for Evaluating the Hidden Probabilities of N - Line Contingencies in Smart Grids - Che, Liang; Liu, Xuan; Wen, Yunfeng; Li, Zuyi (IEEE transactions on smart grid, 2019)
In contingency analysis of large-scale power systems, the high-order contingencies involving a relatively large number of component failures are traditionally assumed to have a very low occurrence probability. However, this may underestimate the probability of some N - {k} contingencies and thus pose risk to the reliable system operations considering that those contingencies would cause severe consequences. In this paper, we investigate the problem of hidden N - {k} contingencies and cast the problem of evaluating the hidden probability of an N - {k} contingency as a mixed integer linear programming problem. The simulation results on the IEEE 14-bus and 118-bus systems verify the effectiveness of the proposed model.